Bee Pollen Polysaccharide From Rosa rugosa Thunb. (Rosaceae) Promotes Pancreatic β-Cell Proliferation and Insulin Secretion - Yang, Siwen; Qu, Yunhe; Chen, Jiyu; Chen, Si; Sun, Lin; Zhou, Yifa; Fan, Yuying (Frontiers in Pharmacology, 2021)
Insufficient pancreatic β-cell or insulin-producing β-cell are implicated in all types of diabetes mellitus. Our previous studies showed bee pollen polysaccharide RBPP-P improves insulin resistance in type 2 diabetic mice by inhibiting liver fat deposition. However, its potential of regulating β-cell function and mass are not fully known. Herein, we observed that β-cell proliferation, insulin synthesis and insulin incretion were intensely activated in MIN6 cells when treatment with RBPP-P. In alloxan-induced diabetic mice, oral administration of RBPP-P effectively decreased the blood glucose, drink intake and urine. It directly stimulated phosphorylation of p38, MAPK and AKT to maintain the islet function and mass. Thus, our data suggest that RBPP-A is a natural compound to regulate β-cell proliferation and function, indicating it might have therapeutic potential against type 1 diabetes.